2018
DOI: 10.1021/jacs.8b04059
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the Limits on Metal–Organic Frameworks as a Catalyst Support: NU-1000 Supported Tungsten Catalysts for o-Xylene Isomerization and Disproportionation

Abstract: Acid-catalyzed skeletal C-C bond isomerizations are important benchmark reactions for the petrochemical industries. Among those, o-xylene isomerization/disproportionation is a probe reaction for strong Brønsted acid catalysis, and it is also sensitive to the local acid site density and pore topology. Here, we report on the use of phosphotungstic acid (PTA) encapsulated within NU-1000, a Zr-based metal-organic framework (MOF), as a catalyst for o-xylene isomerization at 523 K. Extended X-ray absorption fine str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 78 publications
0
58
0
Order By: Relevance
“…However, it is important to note here that a stabilizing effect of the POM on the MOF will only be obtained when the shape, size, and symmetry of the POM match the MOF host [135]. This stabilizing effect even allowed the application of POM@MOF catalysts in aggressive reactions, as was demonstrated in the very nice work of Hupp, Farha, and Notestein [133]. In this study, the Zr-based MOF, NU-1000, was loaded with H 3 PW 12 O 40 for its use in the strong acid-catalyzed reaction of o-xylene isomerization/disproportionation at 250 • C (see Figure 11).…”
Section: Other Organic Transformationsmentioning
confidence: 86%
See 1 more Smart Citation
“…However, it is important to note here that a stabilizing effect of the POM on the MOF will only be obtained when the shape, size, and symmetry of the POM match the MOF host [135]. This stabilizing effect even allowed the application of POM@MOF catalysts in aggressive reactions, as was demonstrated in the very nice work of Hupp, Farha, and Notestein [133]. In this study, the Zr-based MOF, NU-1000, was loaded with H 3 PW 12 O 40 for its use in the strong acid-catalyzed reaction of o-xylene isomerization/disproportionation at 250 • C (see Figure 11).…”
Section: Other Organic Transformationsmentioning
confidence: 86%
“…Phosphotungstic acid encapsulated in NU-1000 for its use in the aggressive hydrocarbon isomerization reaction. Reprinted with permission from[133]. Copyright (2018), American Chemistry Society.…”
mentioning
confidence: 99%
“…The node of the parent framework presents labile protons in the form of ligated hydroxo and aqua groups . The protons are readily displaceable upon introducing reactive metal precursors (molecular complexes) either through a vapor‐phase (in an atomic layer deposition‐like process) or condensed‐phase reaction …”
Section: Introductionmentioning
confidence: 99%
“…Even early, G. Ferey et al have attempted to load the heteropoly acid into MIL-101 super-cage when they reported the MIL-101 [12]. Afterwards, the HPA@MOF composites have continuously being reported on the basis of the MOF type, such as KKUST-1 [13], MIL-101 [14], IRNENU [15], HKUST-1(MOF-199) [16,17], MIL-100 [18], MIL-53 [19], ZIF-8 [20,21], NU-1000 [22,23], UIO-66(Zr) [24,25] and so forth. Among these, UIO-66(Zr) and UIO-66(Zr) analogies which are formed by the Zr 6 (OH) 4 O 4 (CO 2 ) 12 cluster, have drawn more attentions due to the extraordinary chemical and thermal stability [26].…”
Section: Introductionmentioning
confidence: 99%